Measurement of Dry Matter and Starch in Modern Cassava Genotypes during Long Harvest Cycles - Silva, Rudieli Machado da [UNESP]; Fernandes, Adalton Mazetti [UNESP]; Leonel, Magali [UNESP]; Pelvine, Raíra Andrade [UNESP]; Figueiredo, Ricardo Tajra de [UNESP]; Rangel, Marco Antonio Sedrez; Ringenberg, Rudiney; Oliveira, Luciana Alves de; Santos, Vanderlei da Silva; Vieira, Eduardo Alano (My University, 2023)
Starch (ST) is the main determinant of cassava root industrial quality and is routinely quantified using the specific gravity (SG) method, which is simple but lacks precision. This study aimed to estimate the dry matter (DM) and ST content in nine modern cassava genotypes using the SG method and to develop updated empirical equations that relate SG values with DM and ST content. Two field experiments were conducted using a randomized block design with nine genotypes, nine to ten harvest periods, and four replicates. The correlation between root SG and DM was stronger than that between root SG and ST; however, harvest seasonality strongly influenced this relationship. Genotypes varied in their earliness of ST accumulation in the roots, and genotype-specific equations estimated root DM and ST with greater accuracy than equations based on pooled data from all genotypes. Furthermore, the equations from the literature were less accurate in estimating the root DM and ST content than the equations generated in this study. Therefore, these equations can be used by processing industries to improve the predicted cassava root DM and ST content; however, it may be necessary to include the percentage of ST that industries cannot remove from fresh cassava roots during processing.
Keywords: cassava genotypes; harvest seasonality; Manihot esculenta; root quality; specific gravity